Synthesis of medronic acid monoesters and their purification by high-performance countercurrent chromatography or by hydroxyapatite - Puljula, Elina; Vepsäläinen, Jouko; Turhanen, Petri A. (Beilstein Journal of Organic Chemistry, 2016)
We achieved the synthesis of important medronic acid monoalkyl esters via the dealkylation of mixed trimethyl monoalkyl esters of medronic acid. Two methods were developed for the purification of medronic acid monoesters: 1) small scale (10–20 mg) purification by using hydroxyapatite and 2) large scale (tested up to 140 mg) purification by high-performance countercurrent chromatography (HPCCC).
Keywords: bisphosphonate; bisphosphonate monoester; high performance counter current chromatography; hydroxyapatite; medronic acid